2007
DOI: 10.1111/j.1365-2559.2007.02730.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinicopathological significance of oestrogen‐responsive ezrin–radixin–moesin‐binding phosphoprotein 50 in breast cancer

Abstract: Oestrogen-responsive EBP50 may play an important role in tumour progression and might be a potential marker of invasiveness for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 35 publications
7
82
1
Order By: Relevance
“…EBP50 is present at the plasma membrane in physiological conditions, but often displays ectopic cytoplasmic expression in cholangiocarcinoma tumors. Similar cytoplasmic expression of EBP50 has been described in other human carcinomas, including breast, liver (hepatocellular carcinoma), brain and colon (Stemmer-Rachamimov et al, 2001;Shibata et al, 2003;Cardone et al, 2007;Song et al, 2007;Hayashi et al, 2010;Molina et al, 2010). In these tumors, we show an association between EBP50 cytoplasmic expression and the presence of EGFR at …”
Section: Loss Of Ebp50-egfr Interplay In Biliary Carcinomasupporting
confidence: 87%
“…EBP50 is present at the plasma membrane in physiological conditions, but often displays ectopic cytoplasmic expression in cholangiocarcinoma tumors. Similar cytoplasmic expression of EBP50 has been described in other human carcinomas, including breast, liver (hepatocellular carcinoma), brain and colon (Stemmer-Rachamimov et al, 2001;Shibata et al, 2003;Cardone et al, 2007;Song et al, 2007;Hayashi et al, 2010;Molina et al, 2010). In these tumors, we show an association between EBP50 cytoplasmic expression and the presence of EGFR at …”
Section: Loss Of Ebp50-egfr Interplay In Biliary Carcinomasupporting
confidence: 87%
“…Overexpression of NHERF1/EBP50 has been reported in breast cancer (5,6) and in 55% of hepatocellular carcinoma samples (7). Initially, overexpression of NHERF1/EBP50 has been correlated with lower tumor invasiveness in breast cancer cell lines (8).…”
Section: Introductionmentioning
confidence: 99%
“…These two independent studies however reached the same conclusions. They found that EBP50 overexpression is significantly associated with tumor stage, metastatic progression, poor prognosis and ER status (5,9). The expression and distribution of EBP50 are regulated by estrogens and contribute to the proliferative response in biliary epithelial cells (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In tumors, ie, in hepatocellular or breast carcinomas, and in non tumor proliferative tissue such as the endometrium, EBP50 can be overexpressed and redistributed to the cytoplasm and/or nucleus of epithelial cells. [7][8][9][10] In addition, some EBP50 binding partners, eg, platelet-derived growth factor or epidermal growth factor receptors, PTEN, ␤-catenin, and Pin1 signaling molecules, are directly involved in cell proliferation. 8,[11][12][13][14][15] However, the exact impact of EBP50 on cell proliferation remains unclear.…”
mentioning
confidence: 99%